Modified recombinant collagen-peptide/gallic acid grafted chitosan composites with antibacterial and antioxidant property for wound dressing: a preliminary study - Chen, Yu; Wen, Wenjie; Wang, Jie; Huang, Shiting; Ren, Qianqian; Cai, Jiayao; Zhou, Songlin; Li, Rui; Ren, Dandan; Peng, Liaotian; Deng, Chao; Zhang, Jue (Frontiers in Immunology, 2025)
Chronic wounds pose a persistent clinical challenge, primarily due to prolonged bacterial infections. The development of natural antibacterial dressings offers a promising strategy for their effective management. In this study, recombinant human collagen methacrylamide (RHCMA) and gallic acid-grafted chitosan (CSGA) were synthesized and subsequently crosslinked via UV irradiation to form a composite hydrogel (RHCMA-CSGA). The composition and structure of the hydrogel were systematically characterized. Its cytocompatibility and antibacterial properties were also evaluated. The results demonstrated that the hydrogel exhibited excellent biocompatibility and strong antibacterial activity. These findings suggest that the RHCMA-CSGA hydrogel holds great potential as a therapeutic dressing for chronic wound healing.